New forecasting methods in the global economy: AI, geoinformation systems and network analysis - Ivanova, Anna; Skripka, Ivan; Tunik, Maria (InterAção, 2025)
The article analyzes new approaches to forecasting international dynamics in the context of multipolarity and digitalization, focusing on interaction with the regions of the Global South. The research is aimed at overcoming the limitations of traditional methods through the integration of computing technologies into the analysis of complex political and economic processes. The central result is the development of information and analytical tools based on modern digital platforms. This toolkit allows one to operationalize key theoretical concepts such as the multidimensional presence of actors and the spatial determination of their decisions, providing an analysis of patterns of activity and influence in given regions. The use of artificial intelligence and geospatial analysis significantly expands the possibilities of processing large amounts of data, identifying hidden relationships and modeling scenarios. The work contributes to the development of computational social sciences by demonstrating the potential of technologically advanced, regionally oriented approaches for studying global interactions.